The Possible Cytoprotective Effects of Antioxidant Drugs (Vitamin E and C) Against the Toxicity of Doxorubicin in Breast Cancer Patients - Kashkool, Anmar H.; Al-Sabbagh, May S.; Al-Kashali, Dawser K.; Rawaq, Kudair J.Al- (Journal of the Faculty of Medicine Baghdad, 2009)
Background: Breast cancer is the culmination of a multi-step process that occurs over a period of several years or decades and as a cause of death, is a salient "free radical" disease. Aim: The present study aims on investigating the possible protective role of antioxidant drugs (vitamins E and C) to cardiac cells against the oxidative stress induced damage during doxorubicin chemotherapy in patients with breast cancer. Patients and methods: Thirty two patients with different stages of breast carcinoma attending to Baghdad Teaching Hospital and ten healthy control subjects with age range between (29-61) years, mean (43.6±1.37) were included in this study. The patients were randomized into 3 groups, they were treated with either doxorubicin alone 60 mg/M² every 21 days, doxorubicin 60 mg/M² every 21 days +vitamin E 800IU/day for 42 days or a combination of vitamins E 800IU/day and vitamin C 1000mg/day for 42 days + doxorubicin 60 mg/M² every 21days. The oxidative stress and cardiac function parameters were evaluated before starting treatment and after 21 and 42 days respectively including assessment of serum levels of MDA, creatine kinase and lactate dehedrogenase activities. Results: Using doxorubicin alone produce an elevation in the markers of oxidative stress and cardiac damage that can be reduced when antioxidant drugs vitamin E alone or a combination of vitamin E and vitamin C being added. Conclusion: Antioxidant drugs, vitamin E or a combination of vitamins E and C when co-administered with the antineoplastic drug doxorubicin reduces its cytotoxicity on cardiac cells in breast cancer patients.